Sources of Energy Poverty: A Factor Analysis Approach for Spain - Taltavull de La Paz, Paloma; Juárez Tárrega, Francisco; Su, Zhenyu; Monllor, Paloma (Frontiers in Energy Research, 2022)
This paper estimates housing quality and features explaining energy poverty in Spain and its regions. By using the EU-SILC dataset for 2008–2019, the paper calculates the hidden links between energy poverty indicators and housing features, controlled by other variables such as type of household, poverty, and housing tenancy. Confirmatory factor analysis is used to identify the role of different dimensions in explaining energy poverty at the household level. The empirical evidence finds three hidden factors associating energy poverty with: poverty; poor housing quality; and housing size and outskirts location. These three factors enable classifying households accordingly, revealing their distribution across Spain and three of its 17 Spanish regions: Madrid; Cataluña; and Valencian Community. Findings indicate how the impact of energy poverty differs by region, rejecting the general hypothesis that all households in poverty live in poor housing because they cannot afford the maintenance costs, thus causing energy poverty. Results suggest that energy poverty due to poor housing quality and location affects many households that are not necessarily poor, with different impacts depending on location. The association between energy poverty and larger houses located in the outskirts represents new evidence in the literature and is one of the contributions of this paper, together with the methodology for classification. Results suggest that retrofitting investment would be crucial in reducing energy poverty problems in Spain.